Waterproofing behavior of sealing gaskets for circumferential joints in shield tunnels: A full-scale experimental investigation. (February 2021) - Zhang, Gao-Le; Zhang, Wen-Jun; Li, Hong-Liang; Cao, Wen-Zhen; Wang, Bo-Da; Guo, Wei-She; Gao, Pan
Highlights: A full-scale experimental method was proposed for gasket waterproof performance. Four gasket profiles were tested for mechanical and waterproof performance. The gasket mechanical and waterproof performance were discussed in detail. The water leakage phenomenon was investigated compared with that in practice. The detailed leakage process of gaskets was initially interpreted. Abstract: This work was performed to investigate the waterproofing and mechanical behavior of sealing gaskets for circumferential joints in Tianjin metro line Z2 tunnel by a full-scale experiment. A newly developed device was introduced in detail, with test procedures, essential treatment methods, and the adopted specimens for gaskets and reinforced concrete segments. Four types of EPDM and composite cross-section gasket profiles were tested under different combinations of joint openings and offsets. The gasket mechanical performance was examined through the load versus deformation relationship, while the water pressure versus joint opening relationship was applied for identifying the gasket sealant performance. The effect of gasket opening area was then discussed, based on a comparison of the test results from two similar gasket profiles. The ratio of waterproof capacity to average contact pressure was proposed to analyze the correlation between the gasket mechanical and sealant behavior. The results showed that both of the joint opening and offset had a great influence on the gasket waterproof behavior, which generally exhibited a reduction with larger joint opening and offset. A relatively small change in gasket opening area may lead to a greater degree of variation in the gasket mechanical and waterproof performance. The leakage failure analysis indicated that bolt holes, circumferential joints and concrete cracks were the common leakage points during the tunneling construction and operation. The full-scale experimental methodology in this paper had the potential in detecting detailed leakage process of gaskets.